Menelaah Keberhasilan Pendidikan Karakter Di Jepang Untuk Menunjang Program Penguatan Pendidikan Karakter (PPK) Di Indonesia - Arrifah Putri Nadila; Abdal Malik Fajar Alam (Badan Penerbit STIEPARI Press, 2024)
This research explores the success of character education in Japan to support the Character Education Strengthening Program (PPK) in Indonesia. The research method employed is a qualitative approach with a literature review. Firstly, the study elucidates the Japanese education system, which incorporates character education as an integral part of the curriculum. Secondly, the principles of character education in Japan are delineated to provide a profound understanding of the values applied in the development of students' character. Subsequently, the research analyzes the success factors and challenges in character education in Japan, highlighting aspects that can be adopted or avoided in the Indonesian context. Fourth, the potential application of the Japanese character education model in Indonesia is explored, with a focus on positive changes that can occur in the mindset and behavior of students. Finally, implementation efforts in Indonesia are scrutinized through an understanding of the necessary changes in the education system and community support. The results of this research are expected to provide guidance for the implementation of PPK in Indonesia, considering Japan's successful experience in shaping students' character through qualitative and literature-based approaches. This study can serve as a foundation for the development of policies and practices in character education that are more effective and relevant in Indonesia.